Introducing new vaccines in low- and middle-income countries: challenges and approaches. (1st February 2019) - Guignard, Adrienne; Praet, Nicolas; Jusot, Viviane; Bakker, Marina; Baril, Laurence
ABSTRACT: Introduction : The number of new vaccine introductions (NVIs) in low and middle-income countries (LMICs) has markedly increased since 2010, raising challenges to often overstretched and underfunded health care systems. Areas covered : We present an overview of some of these challenges, focusing on programmatic decisions, delivery strategy, information and communication, pharmacovigilance and post-licensure evaluation. We also highlight field-based initiatives that may facilitate NVI. Expert commentary : Some new vaccines targeting populations other than infants require alternative delivery strategies. NVIs impact upon existing supply chain management, in particular vaccines with novel characteristics. A lack of understanding about immunization and misconceptions may be detrimental to NVI, as well as insufficient or poorly trained health care workforce. Many barriers exist to achieving good vaccination coverage. Real-world evaluation of vaccine safety, effectiveness and impact in LMICs may be limited by lack of robust demographic and disease epidemiology data, as well as limited health care and surveillance infrastructure. A thorough planning phase is crucial to define the most suitable delivery strategy based on the vaccine's and country's specificities. A communication plan and social mobilization are essential. Implementation research and innovative approaches applied to logistics, delivery, communication and program evaluation can facilitate NVI.